On the Characteristic Length Scale for the Synthetic Turbulence Based on the Spalart-Allmaras Model (Advances in Applied Mathematics and Mechanics, 2023)
In the hybrid RANS-LES simulations, proper turbulent fluctuations shouldbe added at the RANS-to-LES interface to drive the numerical solution restoring toa physically resolved turbulence as rapidly as possible. Such turbulence generationmethods mostly need to know the distribution of the characteristic length scale of thebackground RANS model, which is important for the recovery process. The approximation of the length scale for the Spalart-Allmaras (S-A) model is not a trivial issuesince the model’s one-equation nature. As a direct analogy, the approximations couldbe obtained from the definition of the Prandtl’s mixing length. Moreover, this paperproposes a new algebraic expression to approximate the intrinsic length scale of theS-A model. The underlying transportation mechanism of S-A model are largely exploited in the derivation of this new expression. The new proposed expression is employed in the generation of synthetic turbulence to perform the hybrid RANS-LES simulation of canonical wall-bounded turbulent flows. The comparisons demonstratedthe feasibility and improved performance of the new length scale on generating synthetic turbulence at the LES inlet.